Potential Ethyl Acetate Fraction of Mangkokan Leaf Extract (Nothopanax Scutellarium) in Hyperglycemic Rats: A Systematic Review - Nasution, Sri Lestari Ramadhani; Ginting, Chrismis Novalinda; Lister, I Nyoman Ehrich (Universitas Aisyah Pringsewu, 2022)
Mangkokan leaves (Nothopanax scutellarium) contain various phytochemicals such as flavonoids and saponins, where these compounds have antioxidant activity that can improve oxidative stress in the body. Treatment of Diabetes Mellitus disease can be done with drugs and herbs, optimal blood glucose control alone cannot prevent complications. The available therapies for DM include insulin therapy and other hypoglycemic agents that can not be separated from various side effects and failure to significantly prevent complications, including the Mangkokan leaf herbal treatment (Nothopanax scutellarin) which has an antidiabetic effect. To systematically review the effect of the ethyl acetate fraction of the extract of the Mangkokan (Nothopanax scutellarium) leaf extract on blood sugar levels, malondialdehyde, insulin expression in pancreatic cells and pancreatic histopathology in hyperglycemic rats. A systematic search was carried out in the PubMed database, Medline, Web of Science, Scopus, EMBASE from 2017 to 2021. The reported results stated that Alloxan is a compound that has diabetogenic properties and is toxic especially to pancreatic beta cells and when administered to animals will cause the rat to be diabetic. Alloxan causes damage to pancreatic beta cells by activating reactive oxygen (ROS) which is initiated by the reduction reaction of alloxan.Daun mangkokan (Nothopanax scutellarium) mengandung berbagai fitokimia seperti flavonoid dan saponin, dimana senyawa tersebut memiliki aktivitas antioksidan yang dapat meningkatkan stres oksidatif dalam tubuh. Pengobatan penyakit Diabetes Mellitus dapat dilakukan dengan obat-obatan dan herbal, pengendalian glukosa darah yang optimal saja tidak dapat mencegah terjadinya komplikasi. Terapi yang tersedia untuk DM antara lain terapi insulin dan agen hipoglikemik lainnya yang tidak lepas dari berbagai efek samping dan kegagalan untuk mencegah komplikasi secara nyata, termasuk pengobatan herbal daun mangkokan (Nothopanax scutellarin) yang memiliki efek antidiabetik. Mengkaji secara sistematis pengaruh fraksi etil asetat ekstrak ekstrak daun mangkokan (Nothopanax scutellarium) terhadap kadar gula darah, malondialdehid, ekspresi insulin pada sel pankreas dan histopatologi pankreas pada tikus hiperglikemik. Penelusuran sistematis dilakukan di database PubMed, Medline, Web of Science, Scopus, EMBASE dari tahun 2017 hingga 2021. Hasil yang dilaporkan menyatakan bahwa Alloxan merupakan senyawa yang memiliki sifat diabetogenik dan bersifat toksik terutama terhadap sel beta pankreas dan bila diberikan pada hewan akan menyebabkan tikus menjadi diabetes. Aloksan menyebabkan kerusakan sel beta pankreas dengan mengaktifkan oksigen reaktif (ROS) yang diawali dengan reaksi reduksi aloksan.